Предмет: Математика, автор: kzkslzosoow

Упростите выражение

12/(x ^ 2 + 12x + 36) + 12/(x ^ 2 - 36) - 1/(x - 6)

Ответы

Автор ответа: Аноним
1

Пошаговое объяснение:

Формулы:

  • a^2-b^2=(a-b)(a+b)\\(a+b)^2=a^2+2ab+b^2\\(a-b)^2=a^2-2ab+b^2

\frac{12}{x^2+12x+36}+\frac{12}{x^2-36}  -\frac{1}{x-6}=\frac{12}{(x+6)^2}+\frac{12}{(x-6)(x+6)} -\frac{1}{x-6}=\frac{12(x-6)+12(x+6)-(x+6)^2}{(x+6)^2(x-6)}  =\frac{12x-72+12x+72-x^2-12x-36}{(x+6)^2(x-6)}=-\frac{x^2-12x+36}{(x+6)^2(x-6)}=-\frac{(x-6)^2}{(x+6)^2(x-6)} =\frac{6-x}{(x+6)^2}

Похожие вопросы
Предмет: Алгебра, автор: zenavasenko12
Предмет: Алгебра, автор: Аноним